Psychotic depression secondary to hyperthyroidism and lethal outcome by thyrotoxic storm: case report - Orihuela-Carpio, Fiorella Stephani (2022)
The role of excess and deficit of thyroid hormone in the pathogenesis of mood disorders has been recorded for almost two centuries. Thyroid pathologies, the most numerous among endocrine diseases, are causally associated with psychiatric pathology in a significant percentage of cases. Specifically, hyperthyroidism produces multiple psychopathological manifestations of anxious and depressive type, manic episodes and, infrequently, psychosis. Although the influence of the thyroid axis on the neural pathways of norepinephrine, dopamine, and serotonin plays a fundamental neurobiological role in these phenomena, there are still multiple underlying mechanisms to be elucidated. Given the need for a broad and comprehensive differential diagnosis between primary and secondary psychiatric pathologies, we report the case of a 52-year-old patient with psychotic depression in whom the late diagnosis of hyperthyroidism had painful and lethal consequences. Clinical and laboratory-based evaluations of thyroid function should be part of the psychiatric evaluation of any person with affective and anxiety disorders.